Sustainability of International Standards Organisation 14001 Standards through Integration with Lean Principles - A. P., Puvanasvaran; M. R., Muhamad (© 2011 Science Publications, 2011)
Both Lean and Environmental Management System (EMS) are key business processes which are employed by companies to enhance their manufacturing process and quality performance. ISO 14001 requires a commitment to continual improvement. Yet it does not prescribe how a company should seek the continual improvement. Lean is a process improvement method that helps companies that use it to continually improve. This study analyses these two systems and provides an understanding of how these processes had contributed in improving business efficiencies. Approach: The research methodology applied in the context of this study involved both primary and secondary research methods in gaining a deeper and practical insight into the issues facing Lean and EMS integration. The primary data collection process involved the use of questionnaires for the purpose of gaining a practical insight into the research issue. The literature review summarized the evidence collected from various secondary sources to enable an understanding of the scope, benefits and application of Lean and EMS systems. Results: The findings contributed to the framing of new conceptual framework that combines benefits of both Lean and EMS principles for enhanced business results. Conclusion: This study concluded that an integrated business model can help organisations realize potential benefits and possibilities in the field of business enhancement.